2011
DOI: 10.4085/1062-6050-46.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Arthrometric Measurement of Ankle-Complex Motion: Normative Values

Abstract: Intervention(s): Each ankle underwent anteroposterior (AP) and inversion-eversion (I-E) loading using an ankle arthrometer.Main Outcome Measure(s): Recorded anterior, posterior, and total AP displacement (millimeters) at 125 N and inversion, eversion, and total I-E rotation (degrees) at 4 Nm.Results: Women had greater ankle-complex motion for all variables except for posterior displacement. Total AP displacement of the ankle complex was 18.79 6 4.1 mm for women and 16.70 6 4.8 mm for men (U 5 3742.5, P , .01).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…The execution of the measurement techniques throughout these studies can be well transferred since the use of the arthrometer is well described and reportedly easy to implement. The normative values for healthy ankles, however, were rarely achieved in the control groups of other publications. Furthermore, the authors reflect upon their very wide range of normative values .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The execution of the measurement techniques throughout these studies can be well transferred since the use of the arthrometer is well described and reportedly easy to implement. The normative values for healthy ankles, however, were rarely achieved in the control groups of other publications. Furthermore, the authors reflect upon their very wide range of normative values .…”
Section: Discussionmentioning
confidence: 81%
“…In a dynamic measurement one group applied 1 kg at a velocity of 1.7 m/s . All authors reported anterior displacement only, except for two authors who used the entire ROM from posterior to anterior as a means of identifying MAI . The anterior displacement measured in CAI patients ranged from 3.2 ± 2.8 mm to 21 ± 2.5 mm, but the application of load differs greatly between the different arthrometers.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, their laxity values at 08 of flexion (8.12 6 2.1 mm) and 908 of flexion (9.73 6 2.3 mm) were nearly identical to those we report. Schwarz et al 13 demonstrated normative values for anterior displacement ranging from 8.59À9.95 mm using 125 N of anterior-loading force (with the knee in full extension). The values at 08 of flexion we obtained fall within this range reported by Schwarz et al 13 These comparative findings point to the importance of standardizing loading forces as well as knee and ankle positioning, especially when we compare research trials.…”
Section: Discussionmentioning
confidence: 99%
“…Testing was based on a previously reported protocol with demonstrated reliability [296][297][298]343 .…”
Section: Ankle -Subtalar Joint Laxitymentioning
confidence: 99%